Accrual Reversals and Company Performance: Analysis of Emerging Market - Baloch, Muhammad Saad; Hassan, Arshad (Asian Journal of Accounting Perspectives, 2016)
This is a pioneering study on total accrual reversals, i.e. long-term reversals and their role in company performance in an emerging market. This study observes the impact of total accrual reversals on company performance more exclusively. The sample consists of 100 non-financial companies listed on the Pakistan Stock Exchange (PSE). The purpose is to examine the role of long-term reversals in the performance of companies by observing the impact of total accrual reversals for the current period as well as the previous period on the earnings as it is used as a proxy for company performance. The Pooled OLS Robust method with Driscoll-Kraay standard errors is used. The result indicates that total accrual reversals of the previous and current period affect the earnings of companies positively. This result rejects the perception that accrual reversal does not predict the earnings in the long-term perspective. The study concludes that the role of reversals of total accruals in the performance of companies is positive, which is beneficial for growing companies in an emerging market. Hence, companies should increase the total accrual reversals to enhance their performance and attract foreign investors. Keywords: Accrual Reversals, Earnings, Emerging market, Pakistan Stock Exchange JEL Classification: M40, M41